1999
DOI: 10.1038/17401
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine induces cancer progression by a cell-autonomous mechanism

Abstract: Malignancy is a common and dreaded complication following organ transplantation. The high incidence of neoplasm and its aggressive progression, which are associated with immunosuppressive therapy, are thought to be due to the resulting impairment of the organ recipient's immune-surveillance system. Here we report a mechanism for the heightened malignancy that is independent of host immunity. We show that cyclosporine (cyclosporin A), an immunosuppressant that has had a major impact on improving patient outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
364
2
15

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,021 publications
(385 citation statements)
references
References 26 publications
4
364
2
15
Order By: Relevance
“…The reverted cells, on the other hand, appeared more rounded and closer to the control cells in morphology (Figure 2c). The morphological changes were similar to those in cyclosporin-treated cells described by Hojo et al (1999), which were also shown to be more invasive. As shown in Figure 2d, the mtDNA-depleted cells exhibited a markedly slower growth rate as compared to control cells, which is characteristic of r 0 and r 7 cells (Desjardins et al, 1985;King and Attardi, 1989;Miranda et al, 1999).…”
Section: Oncogenesupporting
confidence: 66%
See 2 more Smart Citations
“…The reverted cells, on the other hand, appeared more rounded and closer to the control cells in morphology (Figure 2c). The morphological changes were similar to those in cyclosporin-treated cells described by Hojo et al (1999), which were also shown to be more invasive. As shown in Figure 2d, the mtDNA-depleted cells exhibited a markedly slower growth rate as compared to control cells, which is characteristic of r 0 and r 7 cells (Desjardins et al, 1985;King and Attardi, 1989;Miranda et al, 1999).…”
Section: Oncogenesupporting
confidence: 66%
“…Matrix protease cathepsin L is an important marker for invasive tumors (Cuvier et al, 1997;Kim et al, 1998). Similarly, TGFb has been shown to be important in inducing the invasive behavior in several tumor cells including A549 (Hojo et al, 1999;Fujimoto et al, 2001;Hata, 2001). Immunoblot analysis of post-nuclear protein fraction (Figure 5a) showed that the levels of both cathepsin L and TGFb are three to six times higher in mtDNA-depleted cells.…”
Section: Effect Of Mtdna Depletion On Atp Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are provocative in light of the high incidence of cancer that accompanies the use of CsA in organ transplant patients (50). Hyperactivation of protein tyrosine kinases, including Itk, during clinical use of PPIase inhibitors may contribute to unregulated cellular proliferation and ultimately formation of malignancies in immunosuppressed patients.…”
Section: Discussionmentioning
confidence: 99%
“…Different reports suggest that therapy with immunosuppressors can specifically stimulate the transcription of genes that may contribute to the onset of complications arising from therapy. In par-ticular, CSA increases transcription of the transforming growth factor ␀ gene, suggesting that CSA may induce tumors in part due to overexpression of this immunosuppressive cytokine (13,14). The finding that CSA up-regulates gene expression in cells from different tissues irrespective of their activation state suggests that calcineurin may be the ubiquitous target, which could then affect gene expression either negatively or positively.…”
mentioning
confidence: 89%